Perception of the local community toward the yellow-crested cockatoo Cacatua sulphurea abbotti), a critically endangered species in Masakambing Island, Indonesia - Ihsannudin,; Hidayat, Kliwon; Sukesi, Keppi; Yayuk Yuliati, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The yellow-crested cockatoo is an endangered species with habitat is in a non-conservation area with community ownership. The local community’s action is determined by perception related to the information about this animal. The study aimed to find out the perception of the local community of Masakambing Island to the yellow-crested cockatoo based on community structure and the advantages-disadvantages aspect. The study was conducted in Masakambing Island, Masalembu sub-district, Sumenep Regency, East Java Province, Indonesia. Quantitative and qualitative data were obtained from observations, closed interviews with the 160 respondents and open interviews with the key informants (local figures, government and non-government elements) and Focus Group Discussion (FGD). This study used mixed methods with convergent parallel mixed-methods design. The results showed that the community structure is a fatalist one with a nature capricious perception. The community has limited life choices and is controlled by other powers. Unsurprisingly, the local community does not have a vision or carry out any real action to conserve this animal. Meanwhile, the community has a perception that the yellow-crested cockatoo has more advantages than disadvantages. The implication is that added-benefits of alternative livelihood for the community based on yellow-crested cockatoo are required. Then, all of the community members can access the benefits of resources, especially based on the existence of the yellow-crested cockatoo.